Development and use of a cognitive system model for solving problems of purposeful behavior - A. A. Solodov; V. M. Trembach (Статистика и экономика)
The aim of the study is to formulate a formal definition of the cognitive system on the basis of a simplified representation of human cognitive activity and on this basis to develop methods for engineering design of the cognitive system model. The process of cognition is modeled as the interaction of several structures of the human personality. The main structures that directly implement the process of cognition are the subconscious mind and the consciousness interacting with it. Using the technique of engineering design of the cognitive model, the architecture of the intellectual system using the cognitive planning mechanism of control actions is developed. An agent-oriented approach was chosen to implement the cognitive mechanism of control actions formation. The algorithm of formation of purposeful behavior adaptation plans of intellectual system is investigated. The knowledge base of the intelligent system is built with the adaptation of purposeful behavior.The method of research is the application of the principles of the theory of dynamic automatic control systems to the simplified processes of cognition and the synthesis of algorithms and technical devices on this basis. The development of an intelligent system of purposeful behavior was conducted on the basis of an agent- oriented approach. To describe the mechanism of purposeful behavior, an integrated approach to knowledge representation is used, combining the advantages of logical and network methods. The main results of the work are the development of a formal definition of a cognitive system in the form of an automatic control system in the state space. The subconscious is modeled by the space of states of the cognitive system, formed as a result of interaction with the outside world. The process of cognition is presented in the form of evaluation by consciousness of the elements of the space of states, which is called the space of evaluations. Interaction with the outside world is modeled both in the form of management of the outside world, and in the form of its informing. On the basis of these representations the structure of the intellectual system realizing the cognitive mechanism of planning of control actions is developed. The architecture of multi-agent system of control actions formation for purposeful behavior is presented. The knowledge base for the formation of adaptation plans of purposeful behavior of the intellectual system is developed.For the key procedures of the cognitive system functioning, the concepts of optimal estimates of state vectors and optimal control process are introduced, which allow to synthesize the best in a certain sense algorithms and technical devices. The use of this technique allowed developing a structure of an intelligent system that implements cognitive mechanism for the planning of control actions; the multi-agent system architecture of formation control actions for goal-directed behavior; knowledge base of intellectual system for planning control actions. The intelligent system was developed using multi-agent technology. Subsystems were formed in the form of separate functional formations-multi-agent systems.